Junctional Adhesion Molecule-Like Protein Promotes Tumor Progression and Metastasis via p38 Signaling Pathway in Gastric Cancer - Fang, Yuying; Yang, Jianmin; Zu, Guohong; Cong, Changsheng; Liu, Shuai; Xue, Fei; Ma, Shuzhen; Liu, Jie; Sun, Yuping; Sun, Meili (Frontiers in Oncology, 2021)
Junctional adhesion molecule-like protein (JAML), a newly discovered junctional adhesion molecule (JAM), mediates the adhesion and migration processes of various immune cells and endothelial/epithelial cells, ultimately regulating inflammation reaction. However, its role in tumors remains to be determined. The expression of JAML was examined in gastric cancer (GC) and peritumoral tissues from 63 patients. The relationship between JAML expression and clinical characteristics was also observed. In vitro, GC cell migration and proliferation were assessed by wound healing assay, transwell migration assay and EdU incorporation assay. Immunohistochemical staining results showed that JAML expression level was higher in GC tissues than in peritumoral tissues. High expression of JAML in cancer tissues was associated with worse cell differentiation, local lymph node involvement, deep infiltration, and advanced stage. In vitro, we found that JAML silencing inhibited GC cell migration and proliferation, while JAML overexpression promoted GC cell migration and proliferation, partially via p38 signaling. Taken together, our study revealed a critical role for JAML to promote GC cell migration and proliferation. JAML might be a novel diagnostic biomarker and therapeutic target for GC.